Meloscaphander grandis (Heterobranchia: Cephalaspidea), a deep-water species from the North Pacific: Redescription and taxonomic remarks - Chaban, Elena M.; Ekimova, Irina A.; Schepetov, Dimitry M.; Chernyshev, Alexei V. (Zootaxa, 2019)
Meloscaphander grandis is a little-known species missing from databases and papers on taxonomic revision and phylogenetic analysis of Scaphandridae. This species is redescribed herein, based on the type specimen and specimens from the abyssal plain adjacent to the Kuril-Kamchatka Trench. A phylogenetic analysis of COI, 16S, and 28S markers show M. grandis to nest within the Scaphander clade. Additionally, Scaphander lignarius and S. bathymophilus are suggested to be a complex of cryptic species. Morphological differences between the genera Meloscaphander and Scaphander are of dubious significance and, when coupled with molecular data, give a strong reason for reconsidering Meloscaphander as a junior synonym of Scaphander. Thus, according to an integrative taxonomic analysis, Meloscaphander grandis has been transferred to the genus Scaphander. The diagnosis of the genus Scaphander is expanded. We propose new combinations as follows: Scaphander grandis (Minichev, 1967) comb. n. for Meloscaphander grandis, Scaphander sibogae (Schepman, 1913) comb. n. for Meloscaphander sibogae, and Scaphander imperceptus (Bouchet, 1975) comb. n. for Meloscaphander imperceptus. Due to the homonymy of Scaphander sibogae Schepman, 1913 (with a sunken spire) and Scaphander sibogae (Schepman, 1913) comb. n. (with an elevated spire), the name S. attenuatus Schepman, 1913 becomes valid for the former species (with a sunken spire).